Analysis of the Biography and Works of Fathollah Shirazi - Anaraki, Arezoo; Rajabi, Mohammadali (Journal of History Culture and Art Research, 2017)
The present research objective, is to introduce" Fathollah Shirazi" as one of the most influential artists in field of lacquer painting. In order to recognize its life and his artistic characteristics, his existing works in the domestic and foreign museums, written references in terms of style, design, implementation, and the paintings’ subject were studied. This article seeks answers to the questions of that who was Fathollah Shirazi? And what features in his works are distinguished him from his counterparts? Fathollah Shirazi was the master painter of lacquer works in the era of Naser-Al-Din Shah Qajar. He has also the honor to receive the title of "Naqashbashi". In addition to painting, this artist had profession in the field of calligraphy and implementation of delicate Halkari technique, which is implementing motifs with gold. Two manuscripts have been written by him that was found in course of the study. In the explanation of his works, he has composed good poems. From his way followers can be named as Farajollah, his son, and Mustafa, the painter of his era. This study was carried out based on the descriptive and analytical method and the research principles gathering was in terms of library method.